2012
DOI: 10.1002/etc.1836
|View full text |Cite
|
Sign up to set email alerts
|

Toxic concentrations in fish early life stages peak at a critical moment

Abstract: During the development of an embryo into a juvenile, the physiology and behavior of a fish change greatly, affecting exposure to and uptake of environmental pollutants. Based on experimental data with sole (Solea solea), an existing bioaccumulation model was adapted and validated to calculate the development of concentrations of persistent organic pollutants in the tissue of developing fish. Simulation revealed that toxic tissue concentrations of pollutants with log octanol-water partition ratio (K(OW)) > 5 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…Görge and Nagel (1990) demonstrated for lindane that eggs showed a lower uptake than later larval stages. A study by Foekema et al (2012) demonstrated that fish eggs had a lower uptake and excretion of PCBs compared to newly hatched larvae. Given the presence of the chorion (hatching does not occur before 48 hpf) the slower uptake may be related to the presence of the PVS and its function as a diffusion boundary layer.…”
Section: Discussionmentioning
confidence: 98%
“…Görge and Nagel (1990) demonstrated for lindane that eggs showed a lower uptake than later larval stages. A study by Foekema et al (2012) demonstrated that fish eggs had a lower uptake and excretion of PCBs compared to newly hatched larvae. Given the presence of the chorion (hatching does not occur before 48 hpf) the slower uptake may be related to the presence of the PVS and its function as a diffusion boundary layer.…”
Section: Discussionmentioning
confidence: 98%
“…The onset of delayed mortality coincided with the transition from yolk-sac to the free-feeding larval stage, the moment when the yolk lipids become depleted. The associated release of lipid-stored organic substances leads to a high peak in the internal exposure concentrations (Foekema et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The mesocosms were installed with about 20 cm of natural sandy sediment that was collected from the coastal North Sea and a 150 cm deep water column of natural seawater collected from the Oosterschelde, a relatively pristine tidal bay in direct connection with the North Sea, often used as a reference site in marine ecotoxicological studies in the Netherlands (e.g. Kuiper et al, 2007;Foekema et al, 2008Foekema et al, , 2012. Concentrations of selected metals measured in the batch of water used for this study were 0.2 μg Cd/L, 1.26 μg Ni/L, 0.5 μg Pb/L, 59 μg Zn/L and 1.1 μg Cu/L.…”
Section: Mesocosmsmentioning
confidence: 99%